Determination of the presence/absence of the Small Hive Beetle (A. tumida Murray) in bee farms of Apis mellifera scutellata in Costa Rica. - Umaña Arguedas, Cliff (2015)
A study was conducted to determine the presence/absence of the small hive beetle SHB Aethina tumida in apiaries in Costa Rica. The aim of this study was to sample hives of Apis mellifera scutellata in the most vulnerable areas due to their proximity to the neighboring country to the north, while the sampling method in the rest of the country was random. Samples were taken between June and October 2014. A total of 637 samples were analyzed from apiaries from four provinces in Costa Rica (Alajuela, San José, Puntarenas, and Guanacaste).  No SHB was detected in any of these samples. These results are discussed.